Intelligent system for testing of object information state - Ivakhiv, O.; Mushenyk, P.; Bazylevych, O. (2011 IEEE 6th International Conference on Intelligent Data Acquisition and Advanced Computing Systems, 2011)
The observed measuring processes are sampled by a multiplex measuring system based at the adaptive commutation principle. The object state numerical reflecting unit processes non-redundant samples. The numerical procedure makes it possible to yield a concrete number associated with its vector presentation. The information uncertainty numerical coding algorithm and its practical realization have been found. It enables us to perform a current real time object state testing.